2012
DOI: 10.1371/journal.pone.0039174
|View full text |Cite
|
Sign up to set email alerts
|

Thaliporphine Preserves Cardiac Function of Endotoxemic Rabbits by Both Directly and Indirectly Attenuating NFκB Signaling Pathway

Abstract: Cardiac depression in sepsis is associated with the increased morbidity and mortality. Although myofilaments damage, autonomic dysfunction, and apoptosis play roles in sepsis-induced myocardial dysfunction, the underlying mechanism is not clear. All of these possible factors are related to NFκB signaling, which plays the main role in sepsis signaling. Thaliporphine was determined to possess anti-inflammatory and cardioprotective activity by suppressing NFκB signaling in rodents. The purpose of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…An increased serum cTnI concentration was reported in dogs with systemic inflammatory response syndrome [16]. In a study on rabbit endotoxemia, serum cTnI concentrations increased after LPS infusion [21]. Serum cTnI concentrations in the present study also increased.…”
Section: Discussionsupporting
confidence: 67%
“…An increased serum cTnI concentration was reported in dogs with systemic inflammatory response syndrome [16]. In a study on rabbit endotoxemia, serum cTnI concentrations increased after LPS infusion [21]. Serum cTnI concentrations in the present study also increased.…”
Section: Discussionsupporting
confidence: 67%
“…Since mTOR is known to be the main regulator of protein translation, changes in the mTOR activity in the brain region exerts a significant impact on pain symptoms, possibly in relation to pelvic pain of CP (Cho et al, 2018). A previous study reported that mTOR could negatively regulate NF‐κB activation and the MMP9 expression in the cells to reduce inflammatory responses (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that mTOR could negatively regulate NF-κB activation and the MMP9 expression in the cells to reduce inflammatory responses (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thaliporphine can recover the impairment of left ventricular systolic function after lipopolysaccharide injection, which is consistent with the reduction in LDH concentration, as well as TNF-α and caspase3 dependent cell apoptosis. Further study shows that thaliporphine protects against myocardial dysfunction both preload-dependently and –independently in lipopolysaccharide-induced endotoxemic rabbits, possibly by up-regulating the PI3K/Akt/mTOR pathway and down-regulating the p38 MAPK/NF-κB pathway [ 90 ]. These observations indicate that thaliporphine may be a novel agent for attenuating endotoxin-induced metabolic disorders with organ injury.…”
Section: Potent Restoration Of Intestinal Microbiota-mediated Metabolic Syndromementioning
confidence: 99%